“Flyable” Guidance and Control Algorithms for Orbital Rendezvous Maneuver - Elisa Capello; Fabrizio Dabbene; Giorgio Guglieri; Elisabetta Punta (SICE Journal of Control, Measurement, and System Integration, 2018)
Rendezvous orbital maneuvers are planned operations which intend to make two spacecraft meet, while avoiding collisions. Aspects such as trajectory safety and robustness, as well as obstacle avoidance, are fundamental for the mission success. The aim of this paper is to provide an overview of some recent algorithms for guidance and control systems, and also their combined exploitation, which can provide significant enhancements. This overview focuses on those algorithms that are characterized by key selected features: the discussed schemes guarantee low computational effort, low fuel consumption, and high safety and robustness. Different experimental setups, which can be used to evaluate the performance of the considered algorithms, are also taken into account and presented.